1985
DOI: 10.1515/tjj.1985.2.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Shear Layer Mixing for Low Emission Gas Turbine Primary Zones

Abstract: Shear layer turbulent fuel and air mixing has been utilised in a simulated gas turbine primary zone combustor. Two methods of fuel injection and two values of the number of air injection holes have been investigated at a constant pressure loss of 4% at a reference Mach number of 0.047. The method of fuel injection and the number of air injection holes was found to influence the flame stability and NO x emissions. A large number of holes produced much higher NO x emissions which was not compensated for by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The Jet Mix design is a form of shear layer stabilised flame and the main variation in equivalence ratio occurs in the jet shear layers. The importance of local shear layer mixing effects on gaseous emissions has been reported previously (15).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The Jet Mix design is a form of shear layer stabilised flame and the main variation in equivalence ratio occurs in the jet shear layers. The importance of local shear layer mixing effects on gaseous emissions has been reported previously (15).…”
Section: Introductionmentioning
confidence: 66%
“…In an associated programme of work to the present the gaseous emissions from this type of combustion system has been studied. This has involved both premixed and direct gas and liquid fuel injection tests (7)(8)(9)(10)(11)14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Low NOx emissions have been demonstrated for non-swirling jet shear layer systems for both gas and liquid fuels (Abdul- Aziz et al, 1987 andAbdul Hussain et al, 1988) and for swirl stabilised systems Andrews, 1988, 1989). The Grid Mix technique of directly fuelling an array of shear layers was shown to have low NOx characteristics Al Dabagh et al, 1983Dabagh et al, , 1985Dabagh et al, , 1989 and the present work investigates techniques to produce further reductions in NOx emissions using lower primary zone air flows for enhanced overall combustor stability.…”
Section: Introductionmentioning
confidence: 91%
“…Al- Dabagh et al (1983Dabagh et al ( , 1984 have shown that increasing the pressure loss at a constant Mach number, by increasing the stabiliser blockage, produces an increase in the turbulence fuel and air mixing. The turbulent velocity was proportional to the square root of the fractional pressure loss and the turbulence dissipation energy which governs the molecular mixing was proportional to the pressure loss to the 1.5 power.…”
Section: Influence Of Pressure Loss At Constant Mach Numbermentioning
confidence: 99%
See 1 more Smart Citation